Sharps Injuries among Nurses in a Thai Regional Hospital: Prevalence and Risk Factors - Honda M (2013)
Background: Sharps injuries (SIs) are one of the most serious occupational accidents among nurses due to the possible severe consequences, such as the transmission of infectious diseases and inducing of mental impairment. Objective: To discover the prevalence of SIs among nurses in a regional hospital in Thailand and to identify factors associated with SIs. Methods: A cross-sectional study was conducted in 2011. Stratified random sampling was used to select the respondents, with wards as the strata and the number of nurses selected proportional to the size of the ward nurse population. 261 self-administered questionnaires were distributed to nurses who used needles, syringes or other sharp medical equipment in their work. Data were analyzed using chi-square tests, correlation analysis and multiple logistic regression analysis. Results: The prevalence of SIs for the previous 12 months was 55.5% among the 250 nurses who returned a completed questionnaire. Of these, 91.1% were with blood. Needles (52.8%) were the main cause of SIs. The reporting rate of SIs to the hospital was 23.8%. SIs had a significant association with each of marital status, work duration, work department, attitude regarding SI prevention, and preventive management. Using multiple logistic regression analysis, attitude was found to be the strongest predictor of SIs when adjusted for other factors. Nurses who had negative attitudes towards prevention of SIs were nearly two times more likely to have SIs than those with positive attitudes (adjusted odds ratio=1.86; 95% CI: 1.03–3.38). Conclusion: The study showed a high prevalence of SIs, but a low reporting rate. This suggests the reporting system requires simplification and also should include a quick response management component. Promoting positive attitudes to SI prevention, and improving the reporting system would reduce SIs.